Alpha-tocopherol content in 62 edible tropical plants - Ching, Ling Soon; Mohamed, Suhaila (American Chemical Society, 2001)
Vitamin E was determined by the high-performance liquid chromatography (HPLC) method. All the plants tested showed differences in their α-tocopherol content and the differences were significant (p < 0.05). The highest α-tocopherol content was in Sauropus androgynus leaves (426.8 mg/kg edible portion), followed by Citrus hystrix leaves (398.3 mg/kg), Calamus scipronum (193.8 mg/kg), starfruit leaves Averrhoa belimbi (168.3 mg/kg), red pepper Capsicum annum (155.4 mg/kg), local celery Apium graveolens (136.4 mg/kg), sweet potato shoots Ipomoea batatas (130.1 mg/kg), Pandanus odorus (131.5 mg/kg), Oenanthe javanica (146.8 mg/kg), black tea Camelia chinensis (183.3 mg/kg), papaya Carica papaya shoots (111.3 mg/kg), wolfberry leaves Lycium chinense (94.4 mg/kg), bird chili Capsicum frutescens leaves (95.4 mg/kg), drumstick Moringa oleifera leaves (90.0 mg/kg), green chili Capsicum annum (87 mg/kg), Allium fistulosum leaves (74.6 mg/kg), and bell pepper Capsicum annum (71.0 mg/kg). α-Tocopherol was not detected in Brassica oleracea, Phaeomeria speciosa, Pachyrrhizus speciosa, Pleurotus sajor-caju, and Solanum melongena.